Analysis of the Relevance of the Illustrated Folklore Book "Jaka Tarub and Jaka Tingkir'' in Instilling Character Values ​​for Elementary School Students: Analisis Relevansi Buku Cerita Rakyat Bergambar “Jaka Tarub dan Jaka Tingkir’’ dalam Menanamkan Nilai-nilai Karakter Siswa Sekolah Dasar - Purnia, Indah; Supryadi, Supryadi (Indonesian Journal of Education Methods Development, 2021)
This research is motivated by the value of characters in the illustrated folklore book "Jaka Tarub and Jaka Tingkir" in instilling character values ​​for grade II Elementary Schools. This study aims to determine the concept of character values ​​in the illustrated people's books of "Jaka Tarub and Jaka Tingkir" and to instill character values ​​in grade II Elementary Schools. This study uses a qualitative research type approach. The data sources of this research are the theory of secondary and primary data obtained from the illustrated folklore book "Jaka Tarub and Jaka Tingkir" in 2017. The data collection method uses content analysis or content analysis. The data analysis technique in this study uses descriptive analysis. The character values ​​of Jaka Tarub's folklore book and Jaka Tingkir's folklore book are analyzed based on the PPK (Strengthening Character Education) which consists of 5 Main Values ​​in the 2013 Curriculum PPK Presidential Decree No. 87 of 2017 namely: (1) Religious, ( 2) Nationalist, (3) Independent, (4) Mutual Cooperation, (5) Integrity. The benefit of this research is to find out the relevance of folklore books with pictures of Jaka Tarub and Jaka Tingkir in instilling character values ​​in second grade elementary school students.